PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN ROKAN HULU - Darmawati, Darmawati; Marnis, Marnis (Jurnal Tepak Manajemen Bisnis, 2017)
The research was conducted at the District Secretariat Rokan Hulu with the aim to determine the effect of Leadership and Organizational Commitment on performance and employee satisfaction.The population is all goverment employees were all civil servants (PNS) in the Regional Secretariat Rokan upstream as many as 97 people, sample collection techniques using methods stratified random sampling and purposive sampling as many as 78 orang.The data used are primary data and secondary data.Teknik collecting data through interviews and questionnaire (questionnaire).This method of analysis used in this research is descriptive quantitative method, namely multiple linear regression analysis two stages with SPSS ver.20.Based on the partial results of the study, leadership variables significantly influence job satisfaction and organizational commitment variables significantly influence job satisfaction employee.Then satisfaction has a significant influenceontheperformancepegawai.